Left ventricular dysfunction in patients with chronic obstructive pulmonary disease - Naja, Mohammad Mostafa; Ibrahim, Abdullah Cheikh; Alkhayer, Mohammad (Journal of medical and pharmaceutical sciences, 2022)
Objective: studying the effects of chronic obstructive pulmonary disease on left ventricle (LV) systolic and diastolic functions. Patients and Methods: A total of 70 cases of diagnosed chronic obstructive pulmonary disease patients (Current smokers or quitters) with 70 age, sex matched healthy control subjects were included in this study. This study was conducted at the Cardiology and pulmonolgy departments in Tishreen University Hospital in Lattakia Syria. All patients with COPD underwent for 2D Echocardiography and the same was done for the controls. . Results: We note a decrease in the mean values of the left ventricular ejection fraction (LVEF) in patients (53.85±6.5) compared to the controls (63.12 ± 4.1%) with (P
Keywords: Chronic obstructive pulmonary disease (COPD); Left Ventricular function; Doppler Echocardiography